Differential Protein Expression During Growth on Medium Versus Long-Chain Alkanes in the Obligate Marine Hydrocarbon-Degrading Bacterium Thalassolituus oleivorans MIL-1 - Gregson, Benjamin H.; Metodieva, Gergana; Metodiev, Metodi V.; Golyshin, Peter N.; McKew, Boyd A. (Frontiers in Microbiology, 2018)
The marine obligate hydrocarbonoclastic bacterium Thalassolituus oleivorans MIL-1 metabolizes a broad range of aliphatic hydrocarbons almost exclusively as carbon and energy sources. We used LC-MS/MS shotgun proteomics to identify proteins involved in aerobic alkane degradation during growth on medium- (n-C14) or long-chain (n-C28) alkanes. During growth on n-C14, T. oleivorans expresses an alkane monooxygenase system involved in terminal oxidation including two alkane 1-monooxygenases, a ferredoxin, a ferredoxin reductase and an aldehyde dehydrogenase. In contrast, during growth on long-chain alkanes (n-C28), T. oleivorans may switch to a subterminal alkane oxidation pathway evidenced by significant upregulation of Baeyer-Villiger monooxygenase and an esterase, proteins catalyzing ketone and ester metabolism, respectively. The metabolite (primary alcohol) generated from terminal oxidation of an alkane was detected during growth on n-C14 but not on n-C28 also suggesting alternative metabolic pathways. Expression of both active and passive transport systems involved in uptake of long-chain alkanes was higher when compared to the non-hydrocarbon control, including a TonB-dependent receptor, a FadL homolog and a specialized porin. Also, an inner membrane transport protein involved in the export of an outer membrane protein was expressed. This study has demonstrated the substrate range of T. oleivorans is larger than previously reported with growth from n-C10 up to n-C32. It has also greatly enhanced our understanding of the fundamental physiology of T. oleivorans, a key bacterium that plays a significant role in natural attenuation of marine oil pollution, by identifying key enzymes expressed during the catabolism of n-alkanes.